Transit Hotel in Transit Oriented Development Area - Achmad Delianur Nasution; Ronaldo Immanuel Lubis (Talenta Publisher, 2018)
According to the Presidential Regulation of the Republic of Indonesia Number 62 The year 2011 on Spatial Plans of Medan, Binjai, Deli Serdang and Karo (Mebidangro), Pinang Baris was included in TOD Route Map. The commercial area will be redesigned by the division of each building function, corresponding to one of TOD's four segmentation divisions [1]. The building designed in this commercial area is a transit hotel due to its location right next to Pinang Baris Terminal, with the dominance of visitors with tourist destinations to Berastagi, Bukit Lawang, Tangkahan, Lake Toba or Aceh. Hotel Transit Pinang Baris is right in front of T.B Simatupangmain street, adjacent to Mall Pinang Baris, and fitted with Pinang Baris Market building. Inter-building integration will be applied to support the factor of commercial function in the built area. By raising the